Determinants of the duration of post-partum amenorrhea in lactating women in a Philippine urban setting - Wong, John Q.
The aim of this study was to assess the influence of breast-feeding on the duration of post-partum amenorrhea.One hundred seventy-four women from an urban hospital in the Philippines were selected for this study. They recorded their breast-feeding practices over a 24-hour period once every month and their bleeding status daily. Over a period of at least 12 months of observation, these women accumulated 1777 person-time of follow-up. Cox's proportional hazards model with time-dependent variables was used to determine the relationship between breast-feeding practices and the duration of post-partum amenorrhea.By the 6th and the 12th month post-partum, the probability of remaining in amenorrhea was 21and 10, respectively; 50of the women had experienced bleeding by 4.2 months. In the multivariate analysis, any breast-feeding for less than 9 months, exclusive breast-feeding for less than 3 months, and suckling less than 10 episodes a day increased the risk for bleeding among the women in the study.The duration of amenorrhea in post-partum women can be increased by practicing a longer duration of exclusive breast-feeding and of any breast-feeding and by more frequent suckling episodes. Breast-feeding and LAM education programs can make use of these quantitative guidelines. Future studies could allow a lag period between the breast-feeding behavior and the bleeding episode.